Knowledge and perception of community health volunteers of family planning services towards COVID-19 Disease - Jennifer Anyanti; Anthony Nwala; Chinedu Edward Onyezobi; Emmanuel Ekerrete Udoh; Hasiya Ahmadu; Raymond Songo (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2020)
Background: As at the end of August 2020, the coronavirus disease outbreak has hit more than 50,000 across all the 36 states of Nigeria. Whilst the federal government declared contraception an essential service that can continue to be assessed from health facilities, the fear of contracting the disease and stigma associated to facility visits limit the visit of women to health facilities. Given this issue, the role of community health volunteers trained to provide family planning products and services to women in communities becomes very important. A poor understanding of the disease and its transmission routes among these health volunteers may affect continuous uptake of family planning services and result to spread of the infection in communities. Objective: This study aimed to assess the knowledge and perception of community health volunteers of family planning services towards COVID-19 disease in Nigeria. Methods: A cross-sectional, web-based study was conducted among community health volunteers of family planning services about COVID-19. A 19-item survey instrument was developed and distributed randomly among the volunteers using Survey Solutions weblink. The questionnaire requires between 5 to 10 minutes to complete. A chi-square test was used to investigate the level of association among variables, with significance set at 95%CI. The analysis of variance and independent t-test was used to test significant difference among socio-demographic variables with respect to knowledge and perception scores. Significance is also set at 95% CI. Results: The questionnaire was completed by 366 volunteers out of 832 volunteers offering family planning services in communities. The average age of the respondents was 31.63 ± 7.60 years with majority within the age band of 28-37 years, 288(78.7%) were females, 200(54.6%) were married, 304(83.1%) have tertiary educational qualification and 131(35.8%) were CHEWs, 30(8.2%) were Nurses. Most participant 344 (82%) had a good knowledge of the disease and the average knowledge score was 10.40 ± 1.46 out of a total score of 12. Majority also had a positive (right) perception towards COVID-19 disease 331(90.4%) and the average perception score was 27.77 ± 3.22 out of a total of 35 score. There is a positive correlation (r=0.212**, p=0.000) between knowledge and perception towards COVID-19 disease.  Conclusions: As the increasing number of COVID-19 cases continue to disrupt continuous uptake of family planning services, it is essential to improve the knowledge and perception of the community health volunteers. This improvement in knowledge and perception will ensure adequate precautions are taken to avoid the spread of the disease in communities. Educational Interventions are obviously needed to reach all healthcare including those offering services in communities.